Definición formal de salud en los jóvenes clínicamente sanos de la facultad de medicina humana de la universidad privada de san pedro. chimbote. Perú. 2007 - Quispe Villanueva, Manuel Sixto (2010)
The World Health Organization, is to focus their action on health promotion, is therefore critical to have tools for health assessment. The aim of this study was to make a formal definition of health, with the purpose of estimating the health status value of students of the Faculty of Human Medicine of the University of San Pedro. The sample consisted of 100 clinically healthy young students. To evaluate the health status of students were taken on data of medical examinations that students practice them at the beginning of each semester. In this sense, the psychology and the social aspect of the students are presented as maximal variables to assess the health of students. We obtained the formal definition of health and the mathematic model to calculate the level of health of students, this was done taking into account health indicators such as physiological, psychological and social variables.